Simulations of incompressible fluid flows by a least squares finite element method - Pereira, V. D. [UNESP]; Campos Silva, J. B. [UNESP] (Springer Nature, 2005)
In this work simulations of incompressible fluid flows have been done by a Least Squares Finite Element Method (LSFEM) using velocity-pressure-vorticity and velocity-pressure-stress formulations, named u-p-ω) and u-p-τ formulations respectively. These formulations are preferred because the resulting equations are partial differential equations of first order, which is convenient for implementation by LSFEM. The main purposes of this work are the numerical computation of laminar, transitional and turbulent fluid flows through the application of large eddy simulation (LES) methodology using the LSFEM. The Navier-Stokes equations in u-p-ω and u-p-τ formulations are filtered and the eddy viscosity model of Smagorinsky is used for modeling the sub-grid-scale stresses. Some benchmark problems are solved for validate the numerical code and the preliminary results are presented and compared with available results from the literature. Copyright © 2005 by ABCM.
Keywords: Fluid flows; Large eddy simulation; Least-squares finite element; Navier-Stokes equations; Computer simulation; Finite element method; Flow of fluids; Heat flux; Laminar flow; Navier Stokes equations; Partial differential equations; Reynolds number; Turbulent flow; Viscosity; Cavity flow; Large eddy simulations; Least-squares finite element method (LSFEM); Mass fluxes; Incompressible flow